An Australian hospital's training program and referral pathway within a multi‐disciplinary health–justice partnership addressing family violence. (22nd November 2017) - Forsdike, Kirsty; Humphreys, Cathy; Diemer, Kristin; Ross, Stuart; Gyorki, Linda; Maher, Helena; Vye, Penelope; Llewelyn, Fleur; Hegarty, Kelsey
Abstract: Objective : An innovative health–justice partnership was established to deliver legal assistance to women experiencing family violence who attended an Australian hospital. This paper reports on a multifaceted response to build capacity and willingness of health professionals to identify signs of family violence and engage with referral pathways to on‐site legal assistance. Methods : A Realistic Evaluation analysed health professionals' knowledge and attitudes towards identification, response and referral for family violence before and after training; and use of referral pathways. Results : Of 123 health professionals participating in training, 67 completed baseline and follow‐up surveys. Training improved health professionals' self‐reported knowledge of, and confidence in, responding to family violence and understanding of lawyers' roles in hospitals. Belief that patients should be referred to on‐site legal services increased. Training did not correspond to actual increased referrals to legal assistance. Conclusion : The program built capacity and willingness of health professionals to identify signs of, and respond to, family violence. Increase in referral rates to legal assistance was not shown. Potential improvements include better data capture and greater availability of legal services. Implications for public health : Strong hospital system supports and reliable recording of family violence referrals need to be in place before introducing such partnerships to other hospitals.